Prevalence of Shigella boydii in Bangladesh: Isolation and Characterization of a Rare Phage MK-13 That Can Robustly Identify Shigellosis Caused by Shigella boydii Type 1 - Akter, Mahmuda; Brown, Nathan; Clokie, Martha; Yeasmin, Mahmuda; Tareq, Tokee M.; Baddam, Ramani; Azad, Muhammad A. K.; Ghosh, Amar N.; Ahmed, Niyaz; Talukder, Kaisar A. (Frontiers in Microbiology, 2019)
Shigellosis, caused by Shigella boydii type 1 is understudied and under-reported. For three years, GEMS study identified 5.4% of all Shigella as S. boydii. We showed the prevalent serotypes of S. boydii in Bangladesh and phage based diagnosis of S. boydii type1, a rapid and low-cost approach. Previously typed 793 clinical S. boydii strains were used for serotype distribution. Twenty eight environmental water samples were collected for isolation of Shigella phages. Forty eight serotypes of Shigella and other enteric bacteria were used for testing the susceptibility to phage MK-13. Electron microscopy, restriction enzyme analysis, whole genome sequencing (WGS) and annotation were performed for extensive characterization. S. boydii type1 is the second most prevalent serotype among 20 serotypes of S. boydii in Bangladesh. We isolated a novel phage, MK-13 which specifically lyses S. boydii type 1, but doesn’t lyse other 47 serotypes of Shigella or other enteric bacteria tested. The phage belongs to Myoviridae family and distinct from other phages indicated by electron microscopy and restriction enzyme analysis respectively. MK-13 genome consists of 158 kbp of circularly permuted double-stranded DNA with G+C content of 49.45%, and encodes 211 open reading frames including 4 tRNA-coding regions. The genome has 98% identity with previously reported phage, ΦSboM-AG3 which infects most of the S. boydii and other species of Shigella tested. To our knowledge, MK-13 is the first phage reported to be used as diagnostic marker to detect S. boydii type1, especially in remote settings with limited laboratory infrastructure.